Post-COVID myocarditis diagnosed by endomyocardial biopsy and/or magnetic resonance imaging 2–9 months after acute COVID-19. (14th October 2021) - Blagova, O; Ainetdinova, D H; Lutokhina, Y U A; Novosadov, V M; Rud', R S; Zaitsev, A Y U; Kukleva, A D; Alexandrova, S A; Kogan, E A
Abstract: Purpose: To study clinical features of myocarditis and its possible mechanisms (including persistence of SARS-Cov-2 in the myocardium) in the long-term period after acute COVID-19. Methods: Fifteen patients (8 male and 7 female, mean age 47.8±13.4, 24–65 years) diagnosed with postcovid myocarditis were included in the study. The diagnosis of COVID-19 was confirmed by positive PCR results in 40%, and seroconversion in all patients. The average time of admission after COVID-19 was 4 [3; 7] months, from 2 to 9 months. The diagnosis of myocarditis was confirmed by cardiac MRI in 10 patients and by right ventricular endomyocardial biopsy (EMB) in 6 patients. The PCR for cardiotropic viruses and PCR with immunohistochemical study for SARS-Cov2 detection were used. All patients had study for anti-heart antibodies (AHA), EchoCG, and Holter ECG. Coronary atherosclerosis was excluded in all patients over 40 years (7 coronary angiography, 4 cardiac CT). Results: A clear association of the cardiac symptoms with a previous new coronavirus infection was noted in all patients. The symptoms started 1–5 months following COVID-19. MRI showed subepicardial and intramyocardial LGE, signs of hyperemia, increased T1 relaxation time, edema. AHA levels were increased 3–4-fold in 73%. Two variants of postcovid myocarditis were observed. 1. Arrhythmic variant (n=6) – newly developed frequent supraventricular or ventricular extrasystole, recurrent atrial fibrillation in the absence of systolic dysfunction. 2. Decompensated variant with biventricular heart failure (n=9): the mean LV EF was 34.1±7.8% (23 to 46%), LV EDD 5.8±0.7 cm, EDV 153.8±46.1 ml, pulmonary artery systolic pressure 40.7±11.2 mmHg. In one case, myocarditis was accompanied by IgG4- and ANCA-negative aortitis. SARS-Cov-2 RNA was detected in 4 of 5 myocardial biopsies (in one case the material in the study). The longest period of virus persistence after COVID-19 was 9 months. By using spike and nucleocapsid antibodies, coronavirus was detected in cardiomycytes and macrophages. Data of patients with morphologically proved myocarditis are presented in Table 1. Lymphocytic myocarditis was diagnosed and confirmed immunohistochemically (n=5); giant cell myocarditis with atrial standstill was detected in one more case (Fig. 1). Three patients had also signs of endocarditis, in two cases with parietal thrombosis. Conclusions: COVID-19 can lead to the subacute and chronic myocarditis of varying severity. Post-COVID myocarditis manifests itself in two main clinical forms - isolated arrhythmias and systolic dysfunction with heart failure. Post-COVID myocarditis is characterized by prolonged persistence of coronavirus (up to 9 months in this study, in most patients with decompensated variant) in combination with high immune activity (high titers of AHA), which should be considered as the main mechanisms of its long-term course. Treatment approaches for such myocarditis require investigation. Funding Acknowledgement: Type of funding sources: None.